2020
DOI: 10.1111/ijcp.13552
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of women knowledge and perception about polycystic ovary syndrome and its management in Jordan: A survey‐based study

Abstract: Objectives Polycystic ovary syndrome (PCOS) is a common metabolic and endocrine disorder in females in their reproductive‐age and is associated with clinical complications. The aim of this study was to evaluate the knowledge and perception of women in Jordan about PCOS, its symptoms, diagnosis and treatment. Methods A descriptive, cross‐sectional study that was designed in order to assess female knowledge, and perceptions about PCOS in Jordan. The study was carried out through a validated questionnaire and 227… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 19 publications
7
28
1
Order By: Relevance
“…As observed, women incorporated in this study reported considerably varying degrees of knowledge of PCOS. Twenty percent had inadequate knowledge (0-9), 36.4% had satisfactory knowledge (10)(11)(12)(13)(14)(15)(16)(17), and 43.6% had good knowledge (18)(19)(20)(21)(22)(23)(24). The mean knowledge score was determined to be 15.44 AE 7.26 and was graded as satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As observed, women incorporated in this study reported considerably varying degrees of knowledge of PCOS. Twenty percent had inadequate knowledge (0-9), 36.4% had satisfactory knowledge (10)(11)(12)(13)(14)(15)(16)(17), and 43.6% had good knowledge (18)(19)(20)(21)(22)(23)(24). The mean knowledge score was determined to be 15.44 AE 7.26 and was graded as satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…4 Similarly, 80.6% of participants from another study knew that PCOS greatly benefits from reduced weight. 17 While such a decrease in weight can alone restore the menstrual cycle to its regular rhythm naturally, this strategy cannot be suggested in non-obese or minimally overweight women because of limited data on the role of diet and exercise in this population. 4 As for the participant's perception of the disease, most women agreed that PCOS requires social support and that most women with PCOS have a poor body image.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations